Pd-based catalyst, preparation method thereof and application of Pd-based catalyst in efficient photocatalytic production of H2O2 in pure water
Through the high-temperature reduction treatment of Pd/TiO2 catalyst, SMSI characteristics are formed, which solves the problems of energy density and low stability of photocatalytic production of H2O2, and achieves high-efficiency and stable production of high-purity H2O2 in pure water, reducing costs and environmental impacts.
Patent Information
- Application Number
- CN202411260907.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-10
- Publication Date
- 2024-12-27
AI Technical Summary
The prior art has problems such as energy density, environmental pollution, safety risks and low catalyst stability in photocatalytic production of H2O2, and the need to add sacrificial agents leads to low yield and purity.
Pd/TiO2 catalyst is used to form Pd/TiO2-xH with strong interaction (SMSI) through high-temperature reduction treatment, and photocatalytic production of H2O2 in pure water is carried out to avoid the use of sacrificial agents and improve the stability of the catalyst.
It realizes efficient and stable production of high-purity H2O2 in pure water, improves the recycling life and yield of the catalyst, and reduces production costs and environmental impact.
Smart Images

Figure CN119186553A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of catalysts, and in particular relates to a Pd-based catalyst, a preparation method thereof, and an application thereof in photocatalytic production of H2O2 in pure water. Background Art
[0002] Hydrogen peroxide (H2O2) is of great significance in various industries, including chemical synthesis, medical disinfection, industrial bleaching, and environmental remediation. Currently, the production of H2O2 is mainly achieved by utilizing the excellent hydrogenation ability and O2 affinity of Pd-based catalysts. However, this process is energy intensive and produces secondary pollution, posing a threat to the environment and posing huge safety issues. In addition, the storage and transportation of H2O2 require special facilities, which not only increases costs but also poses safety risks. Therefore, the development of efficient and green in situ H2O2 production methods is of great practical significance, but also has certain challenges.
[0003] Photocatalytic in situ synthesis has attracted widespread attention as a green and safe alternative method for producing H2O2. However, the performance of H2O2 production is low due to the easy recombination of photogenerated charge carriers. In order to solve this problem, it is usually necessary to add a sacrificial agent to the reaction solution to consume the photogenerated electrons (or holes), thereby prompting the holes (or photogenerated electrons) to participate in the reaction. However, the addition of sacrificial agents will cause the produced H2O2 to be impure, which undoubtedly increases the cost of purification. Moreover, blindly using sacrificial agents will not significantly increase the yield of H2O2; at the same time, the general Pd / TiO2 catalyst is not stable and difficult to recycle, resulting in low catalytic efficiency and high catalytic cost. Therefore, it is of great significance to develop a Pd-based catalyst for efficient and stable photocatalytic H2O2 production in pure water without the need for sacrificial agents to produce high-purity H2O2. Summary of the invention
[0004] The purpose of the present invention is to propose a Pd-based catalyst, which can efficiently and stably produce H2O2 in pure water through photocatalysis without the need for a sacrificial agent; another purpose of the present invention is to provide a method for preparing the catalyst; a further purpose of the present invention is to provide the application of the Pd-based catalyst in the efficient photocatalytic production of H2O2 in pure water.
[0005] The technical solutions to achieve the purpose of the present invention are as follows:
[0006] A method for preparing a Pd-based catalyst comprises the following steps:
[0007] S1. TiO2 was added to a PdCl2 aqueous solution, stirred at room temperature and then impregnated, and dried after the impregnation to obtain a yellow solid;
[0008] S2. The yellow solid obtained in step S1 is chemically reduced in a NaBH4 solution, filtered and dried to obtain a Pd / TiO2 photocatalyst precursor;
[0009] S3. The Pd / TiO2 photocatalyst precursor obtained in step S2 is subjected to high-temperature reduction in a 5% H2 / Ar atmosphere, and after the reduction is completed, it is cooled to room temperature to obtain Pd / TiO2-xH having SMSI; wherein x represents the high-temperature reduction temperature.
[0010] The present invention reduces the Pd / TiO2 photocatalyst precursor at high temperature under specific conditions to obtain Pd / TiO2-xH with SMSI, which greatly improves the catalytic efficiency and cycle stability and has application prospects for in-situ catalytic production of H2O2.
[0011] Furthermore, after the TiO2 is added to the PdCl2 aqueous solution in step S1, the mass ratio of TiO2 to PdCl2 in the aqueous solution is 2-8:30-150, the concentration of the PdCl2 solution is 1-5 mg / ml, and the immersion time is 10-14 h.
[0012] Preferably, the TiO2 is rutile.
[0013] Preferably, the drying in step S1 is drying in a constant temperature drying oven at 60° C. for 4 to 8 hours after the impregnation is completed.
[0014] Furthermore, the concentration of the NaBH4 solution in step S2 is 0.1-0.5 mol / L, and after the chemical reduction time is 10-14 hours, it is dried in a constant temperature drying oven at 60°C for 4-8 hours.
[0015] Furthermore, the flow rate of the 5% H2 / Ar introduced in step S3 is 20 ml / min.
[0016] Furthermore, the temperature of the high temperature reduction in step S3 is 450° C. to 1050° C.
[0017] Preferably, the temperatures of the high temperature reduction in step S3 are 450° C., 650° C., 850° C. and 1050° C., respectively, and the heating rate is 2-5° C. / min.
[0018] The invention provides a Pd-based catalyst prepared by the method.
[0019] Since the above-mentioned Pd-based catalyst has high efficiency in catalytic production of H2O2 and has significantly improved catalytic stability, the present invention requests protection for the use of the above-mentioned Pd-based catalyst in catalytic production of H2O2.
[0020] The present invention provides the use of the Pd-based catalyst prepared by the above method in photocatalytic production of H2O2 in pure water, comprising the following steps:
[0021] P1. Take the above Pd-based catalyst in a photoreaction tube, add pure water and then ultrasonicate to disperse the catalyst evenly in the aqueous solution;
[0022] P2. Place the photoreaction tube in step P1 in a multi-channel reactor, stir, and continuously introduce oxygen, and irradiate the photoreaction tube with a 100W mercury lamp.
[0023] Furthermore, the mass volume ratio of the Pd-based catalyst to pure water in step P1 is 0.008 g / 20 ml.
[0024] Furthermore, the illumination time in step P2 is 1 hour, the oxygen flow rate is 10-60 ml / min, and the photoreaction tube is placed in circulating water at 25°C.
[0025] Furthermore, the present invention provides the use of the above-mentioned Pd-based catalyst in degrading antibiotics in sewage, wherein the antibiotics contain sulfamethoxazole, and the H2O2 generated by the Pd-based catalyst reacts with Fe 2+ A Fenton system was constructed to degrade the sulfamethoxazole.
[0026] The beneficial effects of the present invention are as follows:
[0027] (1) The Pd / TiO2-xH photocatalyst with SMSI prepared in the present invention has high efficiency in catalytic production of H2O2, especially in low oxygen concentration conditions, and can produce H2O2 efficiently under 100W ultraviolet light irradiation. Compared with Pd / TiO2, which has only 986.22μmol g -1 h -1 In terms of the yield, when the reduction temperature is 850 °C, the photocatalytic H2O2 production performance of Pd / TiO2-xH gradually improves, and the yield of Pd / TiO2-850H reaches a maximum of 4097.63 μmol g -1 h -1 .
[0028] (2) Compared with Pd / TiO2, the performance loss of the Pd / TiO2-xH photocatalyst with SMSI prepared by the present invention is as high as 51.64% after being recycled for 6 times, while the performance loss of Pd / TiO2-850H is only 9.55% after being recycled for 6 times, which shows good stability.
[0029] (3) The present invention prepares Pd-based photocatalysts with different SMSI intensities by chemical reduction of NaBH4 and high-temperature reduction. As the SMSI intensity increases, the position of the valence conduction band is changed, and the separation efficiency of photogenerated charge carriers is effectively improved, thereby promoting the two-step single-electron reduction of O2 to H2O2 in pure water. This provides new opportunities for the development of Pd-based catalysts for efficient photocatalytic production of H2O2 in pure water, such as antibiotic treatment in sewage. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 It is a schematic diagram of the preparation process, HRTEM image and EELS spectrum of Pd / TiO2 and Pd / TiO2-xH photocatalysts.
[0031] Figure 2 It is the XRD spectra of Pd / TiO2 and Pd / TiO2-xH photocatalysts.
[0032] Figure 3 It is the H2-TPD spectra of Pd / TiO2 and Pd / TiO2-xH photocatalysts.
[0033] Figure 4 Schematic diagram of the valence conduction band of Pd / TiO2 and Pd / TiO2-xH photocatalysts.
[0034] Figure 5 It is the transient photocurrent response diagram of Pd / TiO2 and Pd / TiO2-xH photocatalysts.
[0035] Figure 6 This is a comparison chart of H2O2 yields of Pd / TiO2 and Pd / TiO2-xH photocatalysts.
[0036] Figure 7 This is a comparison chart of the H2O2 production performance of Pd / TiO2 and Pd / TiO2-850H photocatalysts after six cycles of use.
[0037] Figure 8 The H2O2 produced by Pd / TiO2-850H photocatalyst for 1 hour reacts with different Fe 2+ Degradation performance diagram of sulfamethoxazole in Fenton system composed of different concentrations.
[0038] Fig. 9 This is a comparison chart of the H2O2 production performance of Pd / TiO2-850H photocatalyst under different atmospheres.
[0039] Fig.10 DMPO-·O2 of Pd / TiO2 and Pd / TiO2-xH photocatalysts - Signal strength comparison chart. DETAILED DESCRIPTION
[0040] In order to enable those skilled in the art to better understand the scheme of the present invention, the technical scheme in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.
[0041] The reagents or materials involved in this embodiment are all commercially available unless otherwise specified, and the terms involved are all technical terms in the art unless otherwise specified. The terms SMSI: stands for Metal Support Strong Interaction; TiO 2-x Represents TiO2 material with oxygen vacancies; O2 - Intermediate represents: superoxide radical.
[0042] Example 1
[0043] This embodiment provides a method for preparing a Pd-based catalyst, comprising the following steps:
[0044] S1. 0.5 g of commercial rutile TiO2 was added to 3 ml of a 5 mg / ml PdCl2 aqueous solution, and then placed on a magnetic stirrer, stirred evenly at room temperature, and then impregnated for 12 h; after the impregnation, the mixture was dried in a 60 ° C constant temperature drying oven for 6 h to obtain a yellow solid powder;
[0045] S2. The yellow solid obtained in step S1 is chemically reduced in a NaBH4 solution with a concentration of 0.1 mol / L. After the chemical reduction time is 12 h, the solid is transferred to a filtration device, washed three times with ultrapure water, and dried in a constant temperature drying oven at 60°C for 6 h. After filtration and drying, a gray powdery Pd / TiO2 photocatalyst precursor is obtained, which is Pd / TiO2 without SMSI.
[0046] S3. The Pd / TiO2 photocatalyst precursor obtained in step S2 is transferred to a crucible with a lid, placed in a tube furnace, and subjected to high-temperature reduction in a 5% H2 / Ar atmosphere. The reduction temperature is 850°C, the heating rate is 2-5°C / min, and the flow rate of 5% H2 / Ar is 20 ml / min. After maintaining for 1 hour, after the reduction is completed, it is cooled to room temperature, taken out and ground in an agate mortar for 12 minutes to obtain Pd / TiO2-xH with SMSI; the x represents the reduction temperature, and Pd / TiO2-850H is prepared.
[0047] Comparative Example 1
[0048] The preparation method is the same as that of Example 1, except that step 3 is omitted and only the Pd / TiO2 photocatalyst precursor is prepared, as follows:
[0049] S1. 0.5 g of commercial rutile TiO2 was added to 3 ml of a 5 mg / ml PdCl2 aqueous solution, and then placed on a magnetic stirrer, stirred evenly at room temperature, and then impregnated for 12 h; after the impregnation, the mixture was dried in a 60 ° C constant temperature drying oven for 6 h to obtain a yellow solid powder;
[0050] S2. The yellow solid obtained in step S1 is chemically reduced in a NaBH4 solution with a concentration of 0.1 mol / L. After the chemical reduction time is 12 h, the solid is transferred to a filtration device, washed three times with ultrapure water, and dried in a constant temperature drying oven at 60°C for 6 h. After filtration and drying, a gray powdery Pd / TiO2 photocatalyst precursor is obtained, which is Pd / TiO2 without SMSI.
[0051] Example 2
[0052] This embodiment provides a method for preparing a Pd-based catalyst, which is different from Embodiment 1 only in that the high-temperature reduction temperature in step S3 is different, and specifically comprises the following steps:
[0053] S1. 0.5 g of commercial rutile TiO2 was added to 3 ml of a 5 mg / ml PdCl2 aqueous solution, and then placed on a magnetic stirrer, stirred evenly at room temperature, and then impregnated for 12 h; after the impregnation, the mixture was dried in a 60 ° C constant temperature drying oven for 6 h to obtain a yellow solid powder;
[0054] S2. The yellow solid obtained in step S1 is chemically reduced in a NaBH4 solution with a concentration of 0.1 mol / L. After the chemical reduction time is 12 h, the solid is transferred to a filtration device, washed three times with ultrapure water, and dried in a constant temperature drying oven at 60°C for 6 h. After filtration and drying, a gray powdery Pd / TiO2 photocatalyst precursor is obtained, which is Pd / TiO2 without SMSI.
[0055] S3. The Pd / TiO2 photocatalyst precursor obtained in step S2 is transferred to a covered crucible, placed in a tube furnace, and subjected to high-temperature reduction in a 5% H2 / Ar atmosphere. The reduction temperature is 450°C, the heating rate is 5°C / min, and the flow rate of 5% H2 / Ar is 20 ml / min. After maintaining for 1 hour, after the reduction is completed, it is cooled to room temperature, taken out and ground in an agate mortar for 12 minutes to obtain Pd / TiO2-xH with SMSI; the x represents the reduction temperature, and Pd / TiO2-450H is prepared.
[0056] Example 3
[0057] This embodiment provides a method for preparing a Pd-based catalyst, which is different from Embodiment 1 only in that the high-temperature reduction temperature in step S3 is different, and specifically comprises the following steps:
[0058] S1. 0.5 g of commercial rutile TiO2 was added to 3 ml of a 5 mg / ml PdCl2 aqueous solution, and then placed on a magnetic stirrer, stirred evenly at room temperature, and then impregnated for 12 h; after the impregnation, the mixture was dried in a 60 ° C constant temperature drying oven for 6 h to obtain a yellow solid powder;
[0059] S2. The yellow solid obtained in step S1 is chemically reduced in a NaBH4 solution with a concentration of 0.1 mol / L. After the chemical reduction time is 12 h, the solid is transferred to a filtration device, washed three times with ultrapure water, and dried in a constant temperature drying oven at 60°C for 6 h. After filtration and drying, a gray powdery Pd / TiO2 photocatalyst precursor is obtained, which is Pd / TiO2 without SMSI.
[0060] S3. The Pd / TiO2 photocatalyst precursor obtained in step S2 is transferred to a crucible with a lid, placed in a tube furnace, and subjected to high-temperature reduction in a 5% H2 / Ar atmosphere. The reduction temperature is 650°C, the heating rate is 5°C / min, and the flow rate of 5% H2 / Ar is 20 ml / min. After maintaining for 1 hour, after the reduction is completed, it is cooled to room temperature, taken out and ground in an agate mortar for 12 minutes to obtain Pd / TiO2-xH with SMSI; the x represents the reduction temperature, and Pd / TiO2-650H is prepared.
[0061] Figure 1 The preparation schematic diagram and structural characterization diagram corresponding to Examples 1-3 and Comparative Example 1. As can be seen from the figure, as the reduction temperature gradually increases, the covering layer on the surface of the Pd nanoparticles in the high-resolution transmission electron microscopy image gradually thickens. The electron energy loss spectrum results show that the covering layer composition of region II in the high-resolution transmission electron microscopy image is TiO 2-x The gradual increase in the Ti L-edge signal in the electron energy loss spectrum indicates the gradual increase in the SMSI intensity.
[0062] Example 4
[0063] This embodiment provides a method for preparing a Pd-based catalyst, comprising the following steps:
[0064] S1. 0.1 g of commercial rutile TiO2 was added to 3 ml of a 5 mg / ml PdCl2 aqueous solution, and then placed on a magnetic stirrer, stirred evenly at room temperature, and then impregnated for 10 h; after the impregnation, the mixture was dried in a constant temperature drying oven at 60 ° C for 4 h to obtain a yellow solid powder;
[0065] S2. The yellow solid obtained in step S1 is chemically reduced in a NaBH4 solution with a concentration of 0.5 mol / L. After the chemical reduction time is 10 h, the solid is transferred to a filtration device, washed three times with ultrapure water, and dried in a constant temperature drying oven at 60°C for 4 h. After filtration and drying, a gray powdery Pd / TiO2 photocatalyst precursor is obtained, which is Pd / TiO2 without SMSI.
[0066] S3. The Pd / TiO2 photocatalyst precursor obtained in step S2 is transferred to a crucible with a lid, placed in a tube furnace, and subjected to high-temperature reduction in a 5% H2 / Ar atmosphere. The reduction temperature is 500°C, the heating rate is 2°C / min, and the flow rate of 5% H2 / Ar is 20 ml / min. After maintaining for 1 hour, after the reduction is completed, it is cooled to room temperature, taken out and ground in an agate mortar for 10 to 15 minutes to obtain Pd / TiO2-xH with SMSI; the x represents the reduction temperature, and Pd / TiO2-500H with SMSI is prepared.
[0067] Example 5
[0068] This embodiment provides a method for preparing a Pd-based catalyst, comprising the following steps:
[0069] S1. 0.2 g of commercial rutile TiO2 was added to 3 ml of a 5 mg / ml PdCl2 aqueous solution, and then placed on a magnetic stirrer, stirred evenly at room temperature, and then impregnated for 14 h; after the impregnation, the mixture was dried in a constant temperature drying oven at 60 ° C for 8 h, and a yellow solid powder was obtained after drying;
[0070] S2. The yellow solid obtained in step S1 is chemically reduced in a NaBH4 solution with a concentration of 0.5 mol / L. After the chemical reduction time is 14 h, the solid is transferred to a filtration device, washed three times with ultrapure water, and dried in a constant temperature drying oven at 60°C for 8 h. After filtration and drying, a gray powdery Pd / TiO2 photocatalyst precursor is obtained, which is Pd / TiO2 without SMSI.
[0071] S3. The Pd / TiO2 photocatalyst precursor obtained in step S2 is transferred to a covered crucible, placed in a tube furnace, and subjected to high-temperature reduction in a 5% H2 / Ar atmosphere. The reduction temperature is 750°C, the heating rate is 5°C / min, and the flow rate of 5% H2 / Ar is 20 ml / min. After maintaining for 1 hour, after the reduction is completed, it is cooled to room temperature, taken out and ground in an agate mortar for 15 minutes to obtain Pd / TiO2-xH with SMSI; the x represents the reduction temperature, and Pd / TiO2-750H is prepared.
[0072] Example 6
[0073] This embodiment provides a method for preparing a Pd-based catalyst, which is different from Embodiment 1 only in that the high-temperature reduction temperature in step S3 is different, and specifically comprises the following steps:
[0074] S1. 0.5 g of commercial rutile TiO2 was added to 3 ml of a 5 mg / ml PdCl2 aqueous solution, and then placed on a magnetic stirrer, stirred evenly at room temperature, and then impregnated for 12 h; after the impregnation, the mixture was dried in a 60 ° C constant temperature drying oven for 6 h to obtain a yellow solid powder;
[0075] S2. The yellow solid obtained in step S1 is chemically reduced in a NaBH4 solution with a concentration of 0.1 mol / L. After the chemical reduction time is 12 h, the solid is transferred to a filtration device, washed three times with ultrapure water, and dried in a constant temperature drying oven at 60°C for 6 h. After filtration and drying, a gray powdery Pd / TiO2 photocatalyst precursor is obtained, which is Pd / TiO2 without SMSI.
[0076] S3. The Pd / TiO2 photocatalyst precursor obtained in step S2 is transferred to a crucible with a lid, placed in a tube furnace, and subjected to high-temperature reduction in a 5% H2 / Ar atmosphere. The reduction temperature is 1050°C, the heating rate is 5°C / min, and the flow rate of 5% H2 / Ar is 20 ml / min. After maintaining for 1 hour, after the reduction is completed, it is cooled to room temperature, taken out and ground in an agate mortar for 12 minutes to obtain Pd / TiO2-xH with SMSI; the x represents the reduction temperature, and Pd / TiO2-1050H is prepared.
[0077] Test Example 1
[0078] 1. Test Method
[0079] The catalysts obtained in Examples 1-3 and Comparative Example 1 were tested respectively using a high-resolution transmission electron microscope, and the obtained HRTEM images and electron energy loss spectra were analyzed to analyze the morphology of each catalyst and the composition of the covering layer; the catalysts obtained in Examples 1-3 and Comparative Example 1 were tested respectively using an X-ray diffractometer, and the obtained XRD spectra were analyzed to analyze the crystal phase and catalytic activity of each catalyst; the H2-TPD spectra corresponding to the catalysts prepared in Examples 1-3 and Comparative Example 1 were tested using a linear thermal conductivity detector and a mass spectrometer to characterize the adsorption performance of the catalysts for H2; the changes in the valence conduction band positions corresponding to the catalysts prepared in Examples 1-3 and Comparative Example 1 were tested using an ultraviolet-visible diffuse reflectance spectrometer and an electrochemical workstation; the instantaneous photocurrent response diagrams of the catalysts prepared in Examples 1-3 and Comparative Example 1 were tested using an electrochemical workstation to characterize the photogenerated charge carrier separation efficiency of each catalyst; the H2O2 production performance corresponding to the catalysts prepared in Examples 1-3 and Comparative Example 1 was tested using an ultraviolet-visible absorption spectrometer; and the H2O2 produced in Example 1 and different Fe 2+ Degradation performance of the Fenton system formed by concentration on sulfamethoxazole; DMPO-·O2 corresponding to the catalysts prepared in Examples 1-3 and Comparative Example 1 was tested in situ using an electron paramagnetic resonance spectrometer - signal to characterize the catalyst's effect on O2 - The formation of intermediates
[0080] 2. Test results
[0081] The XRD spectra corresponding to Examples 1-3 and Comparative Example 1 are as follows Figure 2 As shown by Figure 2 It can be seen that all samples show rutile TiO2 crystalline phase, but due to the amorphous TiO 2-x The formation of the covering layer leads to a decrease in crystallinity. Generally, the decrease in crystallinity is not conducive to the improvement of catalytic activity. However, due to the unique effect of SMSI, the adverse effects of this process can be ignored, resulting in a gradual increase in catalytic activity with the deepening of SMSI, and the best performance after reduction at 850℃.
[0082] The H2-TPD spectra corresponding to Examples 1-3 and Comparative Example 1 are shown in FIG. Figure 3 As shown by Figure 3 It can be seen that as the SMSI intensity gradually increases, the adsorption performance of the catalyst for H2 gradually weakens. This is because the TiO 2-x The formation of the capping layer hinders the adsorption of H2 on Pd nanoparticles, further demonstrating the gradual formation of SMSI.
[0083] The valence conduction band positions corresponding to Examples 1-3 and Comparative Example 1 are as follows: Figure 4 As shown by Figure 4It can be seen that as the SMSI intensity gradually increases, the position of the valence conduction band of the photocatalyst changes, which is more conducive to the two-electron oxygen reduction process to produce H2O2. - The formation of intermediates.
[0084] The instantaneous photocurrent response diagrams corresponding to Examples 1-3 and Comparative Example 1 are shown in FIG. Figure 5 As shown by Figure 5 It can be seen that as the SMSI intensity gradually increases, the photocurrent intensity gradually increases, indicating that the separation efficiency of photogenerated charge carriers is effectively improved, thereby inhibiting the recombination of photogenerated carriers while promoting the efficient utilization of photogenerated electrons and thus promoting the generation of H2O2.
[0085] Application Example 1
[0086] 1. Experimental Methods
[0087] The application of the Pd-based catalyst prepared by the photocatalysts obtained in the above-mentioned Examples 1-3, Example 6 and Comparative Example 1 in the photocatalytic production of H2O2 in pure water was verified by experiments, including the following steps:
[0088] P1. Take the photocatalyst obtained in Examples 1-3 and Comparative Example 1 in a photoreaction tube, the mass volume ratio of the catalyst to pure water is 0.008g / 20ml, and then add pure water and ultrasound to make the catalyst evenly dispersed in the aqueous solution;
[0089] P2. Place the photoreaction tube in step P1 in a multi-channel reactor, stir, and continuously introduce oxygen at a flow rate of 10 to 60 ml / min. This application example uses 30 ml / min. After 30 minutes of dark reaction to allow oxygen to dissolve in equilibrium, start a 1-hour light reaction. Use a 100W mercury lamp to irradiate the photoreaction tube for 1 hour. Place the photoreaction tube in circulating water at 25°C.
[0090] Every 20 minutes, 1 ml of the reaction solution was taken from the reactor and passed through a 0.22 μm filter membrane to determine the yield of H2O2 produced using the iodine titration method.
[0091] 2. Experimental results
[0092] The comparison of the yield of H2O2 produced by the photocatalysts obtained in Examples 1-3 and Comparative Example 1 is shown in the figure Figure 6 As shown, from Figure 6 It can be clearly seen that when the reduction temperature increases to 1050 °C, the performance decreases significantly, which may be caused by the overlay being too thick due to SMSI or the severe sintering of Pd nanoparticles before the formation of SMSI. Figure 6 It can be seen that the H2O2 yield of Pd / TiO2 without SMSI in pure water is only 986.22 μmol g -1 h -1With the increase of SMSI intensity, its yield increased from 1618.42 μmol g -1 h -1 Increased to 4097.63 μmol g -1 h -1 .
[0093] Application Example 2
[0094] 1. Experimental Methods
[0095] The photocatalyst obtained in Example 1 and Comparative Example 1 and pure water were mixed in a mass volume ratio of 8 mg: 20 ml and placed in a photoreaction tube for 10 minutes of ultrasound to make them uniformly dispersed. The photoreaction tube was then placed in a photoreactor and stirred, and oxygen was introduced throughout the process. After 30 minutes of dark reaction to allow oxygen to dissolve in equilibrium, a 1-hour light reaction was started. Every 20 minutes, 1 ml of the reaction solution was taken from the reactor and passed through a 0.22 μm filter membrane, and the yield of the generated H2O2 was determined by iodine titration. After the reaction was completed, the catalyst was filtered and washed three times with pure water and then dried. Subsequently, the experiment was repeated six times according to the above operating steps to examine its cyclic stability.
[0096] 2. Experimental results
[0097] The comparison of H2O2 production performance of the photocatalyst obtained in Example 1 and Comparative Example 1 after six cycles of use is shown in the figure below. Figure 7 As shown by Figure 7 It can be seen that the performance of Pd / TiO2 without SMSI dropped significantly by 51.64% after six cycles, which may be caused by the loss of Pd. However, the performance of Pd / TiO2-850H with the best SMSI level dropped only by 9.55% after six cycles, which may be due to the loss of TiO 2-x Protection of Pd nanoparticles by the capping layer.
[0098] Application Example 3
[0099] 1. Experimental Methods
[0100] In order to investigate the practical application of H2O2 produced by the photocatalyst obtained in Example 1, 2+ A Fenton system was constructed to degrade sulfamethoxazole. The H2O2 produced by Pd / TiO2-850H in Application Example 1 was added to the samples containing different Fe 2+ The reaction solution was placed in a 10 mmol / L sulfamethoxazole solution. Every 1 minute, 1 ml of the solution was taken out from the reaction solution and placed in a liquid chromatography bottle and then placed in an ultra-high performance liquid chromatograph to detect the concentration of sulfamethoxazole.
[0101] 2. Experimental results
[0102] Example 1 The H2O2 produced by the photocatalysts obtained in different Fe 2+ The degradation comparison of sulfamethoxazole at different concentrations is shown in the figure Figure 8 As shown by Figure 8 It can be seen that with the increase of Fe 2+ With the increase of concentration, the degradation performance of sulfamethoxazole gradually improved.
[0103] Application Example 4
[0104] 1. Experimental Methods
[0105] In order to investigate the mechanism of efficient H2O2 production in pure water by the photocatalyst obtained in Example 1, the Pd / TiO2-850H photocatalyst and pure water were mixed in a mass volume ratio of 8mg:20ml and placed in a photoreaction tube for 10min of ultrasound to make them uniformly dispersed. The photoreaction tube was then placed in a photoreactor and stirred, and oxygen, air and nitrogen were introduced into the whole process. After 30min of dark reaction to allow various gases to dissolve and balance, a 1h light reaction was started. Every 20min, 1ml of the reaction solution was taken from the reactor and passed through a 0.22μm filter membrane, and the yield of H2O2 produced was determined by iodine titration.
[0106] 2. Experimental results
[0107] The comparison of H2O2 production performance of the photocatalyst obtained in Example 1 under different atmospheres is shown in the figure below: Fig. 9 As shown by Fig. 9 It can be seen that the performance of H2O2 production in air atmosphere is lower than that in oxygen atmosphere due to the limited O2 concentration. The yield of H2O2 in nitrogen atmosphere is extremely low, which indicates that SMSI promotes the production of H2O2 through the oxygen reduction pathway.
[0108] Application Example 5
[0109] 1. Experimental Methods
[0110] In order to further investigate the oxygen reduction pathway of the photocatalysts obtained in Examples 1-3 and Comparative Example 1 to efficiently produce H2O2 in pure water, an in-situ test of the electron spin resonance spectrum of 5,5-dimethyl-1-pyrroline-N-oxide (DMPO) as a scavenger was conducted. An appropriate amount of the photocatalyst obtained in Example 1 was added to a methanol solution, and then DMPO was added. The DMPO-·O2 was detected by irradiating the solution for 5 min under light conditions. - Signal.
[0111] 2. Experimental results
[0112] DMPO-·O2 of the photocatalysts obtained in Examples 1-3 and Comparative Example 1 - The signal strength comparison results are as follows: Fig.10 As shown by Fig.10It can be seen that the photocatalyst obtained in Comparative Example 1 produced obvious DMPO-·O2 - The signal indicates that the photocatalyst obtained in Comparative Example 1 generates O2 in two steps of single electrons. - and H2O2. For the photocatalysts obtained in Examples 1-3, DMPO-·O2 - signal, and as the SMSI strength increases, DMPO-·O2 - The stronger the signal, the higher the level of SMSI. This indicates that the formation of SMSI promotes the - The production of H2O2 is promoted.
[0113] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the solution. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents based on the understanding of the present solution without departing from the purpose and scope of the technical solution of the present invention, which should be included in the scope of the claims of the present invention.
Claims
1. A method for preparing a Pd-based catalyst, characterized in that: The steps include: S1. TiO2 was added to a PdCl2 aqueous solution, stirred at room temperature and then impregnated, and dried after the impregnation to obtain a yellow solid; S2. The yellow solid obtained in step S1 is chemically reduced in a NaBH4 solution, filtered and dried to obtain a Pd / TiO2 photocatalyst precursor; S3. The Pd / TiO2 photocatalyst precursor obtained in step S2 is subjected to high-temperature reduction in a 5% H2 / Ar atmosphere, and after the reduction is completed, it is cooled to room temperature to obtain Pd / TiO2-xH having SMSI; wherein x represents the high-temperature reduction temperature.
2. The method for preparing a Pd-based catalyst according to claim 1, characterized in that: After the TiO2 in step S1 is added to the PdCl2 aqueous solution, the mass ratio of TiO2 to PdCl2 in the aqueous solution is 2-8:30-150, the concentration of the PdCl2 solution is 1-5 mg / ml, and the immersion time is 10-14 h.
3. The method for preparing a Pd-based catalyst according to claim 1, characterized in that: The concentration of the NaBH4 solution in step S2 is 0.1-0.5 mol / L, and after the chemical reduction time is 10-14 hours, it is dried in a constant temperature drying oven at 60°C for 4-8 hours.
4. The method for preparing a Pd-based catalyst according to claim 1, characterized in that: The temperature of the high temperature reduction in step S3 is 450°C to 1050°C.
5. The Pd-based catalyst prepared by the method for preparing the Pd-based catalyst according to any one of claims 1 to 4.
6. Use of the Pd-based catalyst according to claim 5 in catalytic production of H2O2.
7. The use of the Pd-based catalyst according to claim 5 in photocatalytic production of H2O2 in pure water, characterized in that: The steps include: P1. Take the Pd-based catalyst according to claim 5 in a photoreaction tube, add pure water and then ultrasonicate to uniformly disperse the catalyst in the aqueous solution; P2. Place the photoreaction tube in step P1 in a multi-channel reactor, stir, and continuously introduce oxygen, and irradiate the photoreaction tube with a 100W mercury lamp.
8. The use according to claim 7, characterized in that: The mass volume ratio of the Pd-based catalyst to pure water in step P1 is 0.008 g / 20 ml.
9. The use according to claim 8, characterized in that: The illumination time in step P2 is 1 hour, the oxygen flow rate is 10-60 ml / min, and the photoreaction tube is placed in circulating water at 25°C.
10. The use of the Pd-based catalyst according to claim 5 in the degradation of antibiotics in sewage, characterized in that: The antibiotic contains sulfamethoxazole, and the H2O2 generated by the Pd-based catalyst reacts with Fe 2+ A Fenton system was constructed to degrade the sulfamethoxazole.
